Use of a Modified Spatial-Context Memory Test to Detect Amnestic Mild Cognitive Impairment - Wang, Hsuan-Min (Public Library of Science, 2013)
In this study we sought to differentiate participants with amnestic mild cognitive impairment (a-MCI) from those with mild dementia of Alzheimer’s type (m-DAT) and normal controls by modifying an existing test of spatial context memory (SCMT) designed so as to evaluate the function of brain regions affected in early m-DAT. We found that participants with a-MCI had better total scores on our modified SCMT than those with m-DAT. Furthermore, the locational memory subtest was able to discriminate between those with a-MCI and m-DAT. Additionally, compared with other screening tests, our spatial context memory test showed high sensitivity and specificity in discerning those with a-MCI from the normal population but, was relatively ineffective in discriminating a-MCI patients from those with m-DAT. We conclude that our modified test of SCMT is an effective tool for discriminating a-MCI from m-DAT and does so by detecting differences in locational memory.